Aplikasi Regresi Complementary Log-Log untuk Menganalisis Tingkat Kejahatan Terhadap Perempuan di Kalimantan Tengah Tahun 2019 - Dhika Aulia Yusram; Neli Agustina (Seminar Nasional Official Statistics, 2021)
The risk of experiencing a crime can unsettle the community in guaranteeing a sense of security. Women are victims who have a vulnerability to experience serious situations when experiencing crime. Central Kalimantan is the province with the highest percentage of women experiencing violence in Indonesia where women experiencing crime increased in 2019. Only 20.01% of the people of Central Kalimantan reported incidents of crime they experienced. The low awareness of reporting crimes to the authorities and increasing crimes against women can increase the potential for women to continue to experience crime. This study aims to analyze the level of crime against women and the factors that influence it in Central Kalimantan in 2019. The results of the study using the complementary log-log method show that marital status, cellphone ownership status, education completed and working status significantly affect crimes against women. the risk of experiencing crime increases if the woman is unmarried, has a cellphone, graduated from college and works. Women are still vulnerable to being in the public area so that the government's attitude is needed in designing crime prevention strategies, it can be in the form of increasing knowledge to the public about the risks of crime and what to do if they experience it.